Tingkat Adopsi Teknologi Pengelolaan Tanaman Terpadu (PTT) di Kabupaten Seluma - Merna Ayu Sulastri; Satria Putra Utama; Ketut Sukiyono (Jurnal Penyuluhan, 2022)
Integrated Plant Management Technology (IPMT) is currently applied by farmers in the village of Rimbo Kedui Seluma District. In the context of agricultural technology adoption, farmers' perception of innovation characteristics becomes very important because it becomes the basis of decision making to accept or reject an innovation. The purposes of this research were to analyze the perception of farmers on innovation, the level of adoption of innovation in farmers in understanding the.technology.component contained in Integrated Plant Management, analyzing what variables affect the level of Technology adoption on rice farmers in Seluma district. The method used in this study was the method of analysis of SEM (Structural Equation Model). Variables used were the characteristics of internal farmers, the perception and level.of.adoption.of integrated plant management technology. The respondents.used in this study were 140 people. The results of the research showed that farmers' perception of integrated plant management technology was..in..medium.category,.farmer adoption rate was in medium category, and variable that affects farmers adopt plant management technology was integrated characteristics of the farmer's internal at 0.44 and the perception of farmers at -0.11, internal characteristics of farmers through the perception of farmers that is equal to 0.00.